Aspekte Amerikanischer Kunst der Gegenwart. : Neue ERwerbungen der Sammlung Ludwig. - Becker, Wolfgang; Nordjyllands Kunstmuseum, Aalborg; Henie-Onstad Kunstsenter, Høvikodden; Mittelrheinisches Landesmuseum, Mainz; Städtische Galerie Schloss Oberhausen, Oberhausen (Aachen : Neue Galerie - Sammlung Ludwig Aachen, 1984)
Ahearn, John ; Basquiat, Jean-Michel ; Borofsky, Jonathan ; Matos, John ; Ellis, Chris "Daze" ; Dennis, Donna ; Fischl, Eric ; McGurr, Leonhard ; Graves, Nancy ; Kushner, Robert ; Fabara, Sandra ; Longo, Robert ; MacConnel, Kim ; Jr., Melvin Samuels ; Pfaff, Judy ; Pitt, Suzan ; Quinones, Lee ; Salle, David ; Schnabel, Julian ; Ablack, Torrick
biografie
Aspekte Amerikanischer Kunst der Gegenwart : Neue Galerie - Sammlung Ludwig, Aachen, August 1984
Duits
boek
Keywords: Amerika